Stroke and Cerebrovascular Disease in Pregnancy: Incidence, Temporal Trends, and Risk Factors. Issue 1 (January 2019) - Liu, Shiliang; Chan, Wee-Shian; Ray, Joel G.; Kramer, Michael S.; Joseph, K.S.; Arbour, Laura; Auger, Nathalie; Darling, Liz; Evans, Jane; Joseph, K.S.; Little, Julian; Lee, Lily; et al.
Abstract : Background and Purpose—: Few studies have examined the epidemiology of stroke in pregnancy, despite the high associated burden of death and disability. We aimed to quantify the incidence, temporal trends, risk factors, and case fatality associated with stroke and cerebrovascular disease in pregnancy. Methods—: All antepartum, peripartum, and postpartum hospitalizations and readmissions within 42 days of delivery in Canada (except Quebec) were obtained from the Canadian Institute of Health Information for the years 2003 to 2016. We assessed temporal trends in stroke and quantified associated risk factors using logistic regression. Results—: Five hundred twenty-four stroke cases were identified among 3 907 262 deliveries (13.4 per 100 000). The majority of cases were hemorrhagic strokes (307 cases, 58.6%) and most occurred in the postpartum period (270 cases, 51.5%). The case fatality rate was 7.4%. Stroke incidence rose from 10.8 per 100 000 in 2003 to 2004 to 16.6 per 100 000 deliveries in 2015 to 2016 ( P =0.002). Risk factors for stroke included older maternal (age ≥40 years; adjusted odds ratio [AOR], 1.7; 95% CI, 1.1–2.6), preeclampsia (AOR, 7.1; 95% CI, 5.3–9.6), eclampsia (AOR, 65.9; 95% CI, 43.6–99.6), maternal congenital heart disease (AOR, 38.1; 95% CI, 22.1–65.8), connective tissue disorders (AOR, 12.6; 95% CI, 6.1–26.9), sepsis (AOR, 7.6; 95% CI, 3.6–16.2), severe postpartum hemorrhage (AOR, 4.7; 95% CI, 2.8–8.0), and thrombophilia (AOR, 4.2; 95% CI, 1.5–12.1). Conclusions—: The rising incidence of stroke in pregnancy, especially during the postpartum period, and its strong association with hypertensive disorders of pregnancy (especially preeclampsia) suggest that follow-up of severe hypertensive patients is required after delivery. Abstract : Supplemental Digital Content is available in the text.